Acheulean technical behaviors in Aldène cave (Cesseras, Hérault, France). (21st July 2016) - Rossoni-Notter, Elena; Notter, Olivier; Simone, Suzanne; Simon, Patrick
Abstract: The cave of Aldène (Cesseras, Hérault, France) is usually known for the preservation of its upper Paleolithic and Mesolithic evidence. However, older occupations are located at the entrance and the collapsed zone of this vast karst network. Unfortunately, companies looking for phosphate had earlier truncated this original filling and only nine Paleolithic stratigraphic outliers (T1 to T9) remained. Repeatedly excavated by the Museum of Prehistoric Anthropology of Monaco, from 1971 until 1998, they mainly registered Acheulean (cf. Tayacian) and Pre-mousterian activities. As interdisciplinary studies and radiometric dating ( 230 Th/ 234 U and ESR) were undertaken, it was possible to set up chronostratigraphic and paleoenvironnemental contexts, which mostly extend from the end of MIS 13 up to MIS 5.5. The results obtained in the different units also allowed the correlation of remote layers. Our recent study has focused on technocomplexes with the aim to update the technical behaviors of the Paleolithic knappers that lived along Cesse River, at the entrance of Aldène cave. Petroarcheology joined to technological and morphofunctional analyses have figured out technical evolution and features, even within the successive lithic Acheulean cultures. The technology and the function of the occupations incited Aldène groups to reorient their economic strategies. They abandoned the available fluviatile resources for more siliceous and remote materials (>6 km). Furthermore, percussion and pebble tools associated sometimes with rare bifacial pieces and large flake tools appear to predominate exclusively in the oldest layers (MIS 13–10). In these assemblages, debitage flakes are obtained by Elementary (unipolar or bipolar), SSDA, semi-tournant non-laminar and Discoïd (MIS 11) methods. Retouched products consist of scrapers, notched tools and points (Quinson, Tayac, bilateral). Based on a relative and comparative technological distribution, the first technical transformation emerges in MIS 9. The industries contain more handaxes, rare cleavers and include the premises of the Levallois concept. Thereafter, those technical way and needs will be confirmed (MIS 7–8) with a clear presence of handaxes, increased Levallois products, decrease of percussion and pebble tools, and absence of large flake tools. In layer B, the identification of Levallois blades production and the presence of a Mousterian point reveal the occurrence of Mousterian knappers (MIS 6). The vast archeostratigraphic sequence of Aldène gives us the opportunity to describe the main technical innovations, such as the appearance of Levallois concept throughout the evidence of old structure settlements (fireplaces, slabbed stone pavement).